Using Extending Concept Through Learning Activity To Improve Students Reading Comprehension In Terms Of Literal Comprehension - Azisiyah, Liza Ain; Ilmiah; Basir, Achmad (Journal of Language Testing and Assessment, 2024)
The purpose of this study was to determine whether the use of ECOLA technique can improve students' reading comprehension in terms of literal comprehension at MA Al-Hidayah Lemoa. This research applied Pre-Experimental design by using Quantitative approach. The population of this stu dy were MA Al-Hidayah Lemoa students consisting of 17 students. Then, the sample of this study is class X taken using total sampling technique consisting of 17 students. The data collection process with pre-test and post-test using multiple choice by analyzing the data using SPSS. The results of the study found that the use of the ECOLA technique in the learning process to improve students' reading comprehension in terms of literal comprehension was considered effective based on the data obtained where the average value of the pre-test was 48.82 and the post-test was 85.88. It can be seen that the average value of the post-test is higher than the average value of the pre-test. And proven again from the results of the "paired sample test" analysis using SPSS with a significance value of 0.000 <0.05. Based on the decision making, if the significance value is smaller than 0.05, H0 is rejected and H1 is accepted. Based on these results, it can be concluded that the ECOLA technique can improve students' reading comprehension in terms of literal comprehension.